Improved direct measurement of Ab and Ac at the Z0 pole using a lepton tag - Abe, K; Abe, K; Abe, T; Adam, I; Akimoto, H; Aston, D; Baird, K; Baltay, C; Band, H; Barklow, T; Bauer, J; Bellodi, G; et al. (2002)
The improved direct measurement of Ab at the Z0 pole using a lepton tag was presented. The measurements were carried out using identified charged leptons from semileptonic decays. The results obtained were found to be in agreement with the standard model predictions and were insensitive to uncertainties in standard model parameters and the top quark and Higgs boson masses.